ANALISIS GANGGUAN (NOISE) DALAM PROSES KOMUNIKASI DENGAN PENERAPAN TEKNOLOGI PADI SAWAH DI DESA PENAPALAN KECAMATAN TENGAH ILIR KABUPATEN TEBO - Matuzzahara, Pitria; Sardi, Idris; Nurfathiya, Pera (Universitas Jambi, 2019)
This study was aimed to find out: (1) the noise in process of communication towards the rice technology application in Penapalan Village Tengah Ilir Sub-district. (2) the level of rice technology application in Penapalan Village Tengah Ilir Sub-district. (3) relationship between noise in process of communication with the rice technology application in Penapalan Village Tengah Ilir Sub-district. This research was conducted from September - October 2017 in Penapalan Village Tengah Ilir Sub-district. The location was determined purposively with criteria farmer who apply the rice technology and who accept aid from goverment. The number of samples in the study were 70 farmers. The data used are primary data and secondary data. Data analysis method used was descriptive analysis with scoring and rank spearman analysis. The research showed the noise inprocess of communication were: technical disorders, semantic disorders, and psychological disorders. The level of rice technology application was high (77,14%). In addition it also found there was a relationship between the noise in process of communication with the rice technology application.